FABRICATION AND ANALYSIS OF NICKEL OXIDE NANOPARTICLES FOR ADVANCED APPLICATIONS - Geetha N B,; Boopathy,; Shobana S,; Sindhuja A., (The Bioscan, 2025)
Nickel oxide (NiO) nanoparticles were successfully synthesized using a novel microwave irradiation technique, employing glycine as a fuel. The synthesized NiO nanopowders underwent comprehensive characterization through powder X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FT-IR), high-resolution scanning electron microscopy (HR-SEM), and room-temperature vibrating sample magnetometry (VSM). XRD analysis confirmed the formation of a single-phase cubic NiO structure. HR-SEM images revealed nanoparticle-like morphology, corroborating the nanoscale nature of the synthesized material. Magnetic measurements via VSM exhibited a weak ferromagnetic behavior, with a saturation magnetization value of 20.93 emu/g, indicating the presence of ferromagnetic interactions at room temperature.